Dissection of the human erythrocyte spectrin molecule using monoclonal antibodies. - Burke, B E (1982)
One IgM and three IgG monoclonal antibodies specific to band 1 of human erythrocyte spectrin have been characterised. The antigenic sites of the IgG antibodies have been identified and mapped by radioimmune labelling of tryptic fragments of spectrin fractionated by SDS slab gel electrophoresis and blotted onto nitrocellulose filters. The binding site of one of these antibodies has also been directly visualised in the electron microscope after low-angle shadowing of the antibody-spectrin dimer complex, and lies at that end of the dimer which is responsible for tetramer formation.